2018
DOI: 10.1002/jctb.5870
|View full text |Cite
|
Sign up to set email alerts
|

Glucose addition‐induced changes in the growth and chemical compositions of a freshwater microalga Chlorella kessleri

Abstract: BACKGROUND In recent years, mixotrophic culture of algal cells has been gaining increasing interest, largely because it offers an efficient means of commercial production of lipids and other value‐added products. In this work, the impacts of glucose addition on the biomass production, chemical composition and fatty acid profiles of Chlorella kessleri were investigated to exploit the relationships between extra organic carbon and changes in the distribution of chemical compositions in algal cells. RESULTS Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…However, in our study, even though glucose was mixotrophically consumed within 6 days, the chlorophyll a and chlorophyll b contents continued to decrease possibly due to nitrogen depletion. Our findings are in line with previous studies, where a decrease in photosynthetic pigments was recorded under mixotrophy 29,47,48 . Interestingly, carotenoid content remained unchanged in the cells at 1.5-1.8 mg/g DCW (Fig.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…However, in our study, even though glucose was mixotrophically consumed within 6 days, the chlorophyll a and chlorophyll b contents continued to decrease possibly due to nitrogen depletion. Our findings are in line with previous studies, where a decrease in photosynthetic pigments was recorded under mixotrophy 29,47,48 . Interestingly, carotenoid content remained unchanged in the cells at 1.5-1.8 mg/g DCW (Fig.…”
Section: Resultssupporting
confidence: 94%
“…Such an increase in pH was due to the fixation of CO 2 by algae causing generation of OHions that are neutralized by H + ions in the media 29,30 . However, when the culture reached early stationary phase with negligible growth and nitrate uptake, the pH dropped due to accumulation of H + ions from the release of organic acids by the cells into the culture media.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For biomass raised mixotrophically in medium SCBH‐I, chlorophyll a and b were 2.94 ± 0.12 and 1.19 ± 0.28 μg/mg DW, respectively and which are 91 and 89% lower than the respective figures obtained for photoautotrophic cultivation (Figure ). According to the previous report, utilization of external carbon source under mixotrophic conditions affect negatively on production of photosynthetic pigments . In another study, glucose inhibited carbon dioxide fixation by 10 folds and resulted in decreased photosynthetic pigment contents under mixotrophic conditions .…”
Section: Resultsmentioning
confidence: 83%
“…In addition, as shown in the TEM images ( Figure 2 G), the thylakoid membranes were less abundant and less compact in MC cells, although the volume of the chloroplasts had no visible defect. Some researchers have reported that glucose has negative impacts on photosynthesis by reducing CO 2 apparent affinity and chlorophyll contents or repressing the expression of proteins, such as chlorophyll-binding proteins evolved in PSII, the PSII reaction center protein D1, and Rubisco in the Calvin cycle [ 26 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%